IDENTIFIKASI SENYAWA TOKSIK EKSTRAK KLOROFORM KULIT BIJI NYAMPLUNG (Calophyllum inophyllum L.) - Sri Rahayu Santi; I Wayan Suirta; Kadek Agus Andika Pratama (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
Identification of active toxic compounds from chloroform extract Nyamplung skin bean (Calophyllum inophyllum L) have been conducted. As much as 2,85 g n-hexane extract, 7,42 chloroform extract, and 4,71 water extract were resulted from 1 kg Nyamplung skin bean. Separation of 2 g chloroform extract using column chromatography (stationary phase: silica gel 60 and mobile phase chloroform-methanol 9,5:0,5) resulted in four fraction with yellowish fraction (0,473 g) as the most toxic fraction (LC50 8,241 ppm). Identification using GC-MS showed that the isolate was hexadecanoic acid (21,02%), 8-octadecenoic acid (59,55%), and oktadecanoic acid(19,43%).